Hormone receptors in gynecological cancers: focus on androgen receptor status - Ifthikar, Mariam Anjum; Kamath, Sanoor Neha; Rajanbabu, Anupama; Nair, Indu R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hormonal therapy and chemotherapy remain the primary treatment modalities for advanced and recurrent gynecologic malignancies. The presence or absence of hormone receptors has significant prognostic value in gynecological cancers. Previous studies have shown that high estrogen receptor (ER) and progesterone receptor (PR) levels in endometrial cancer predict favorable survival, while loss of PR expression in ovarian cancers correlates with recurrence. However, the role of androgen receptors (AR) in these cancers is not fully understood. Methods: This observational study analyzed the immunohistochemical expression of AR, ER alpha (ERα), PR, and p53 in patients diagnosed with gynecologic cancers at a tertiary care center. Hormonal receptor expression was evaluated and correlated with tumor type and histopathological features. Results: Prominent expression of ARs was observed across all categories of gynecological cancers included in the study. The expression profiles of ER, PR, and p53 varied among tumor subtypes, reflecting their potential prognostic and therapeutic significance. Conclusions: Androgens appear to play a role in the pathogenesis of gynecological cancers. Hormonal expression profiling may guide future endocrine therapy strategies and could be considered as a potential salvage treatment option similar to that used in ovarian cancers. These findings underscore the importance of detecting hormone receptor expression in all gynecological malignancies.